Arctigenin, a Natural Lignan Compound, Induces Apoptotic Death of Hepatocellular Carcinoma Cells via Suppression of PI3‐K/Akt Signaling. Issue 10 (28th April 2015) - Jiang, Xiaoxin; Zeng, Leping; Huang, Jufang; Zhou, Hui; Liu, Yubin
ABSTRACT In this study, we explored the cytotoxic effects of arctigenin, a natural lignan compound, on human hepatocellular carcinoma (HCC) cells and check the involvement of phosphatidylinositol 3‐kinase (PI3‐K)/Akt signaling. HCC cells were treated with different concentrations of arctigenin and cell viability and apoptosis were assessed. Manipulating Akt signaling was used to determine its role in the action of arctigenin. Arctigenin significantly inhibited the viability of HCC cells in a concentration‐dependent manner. Arctigenin induced apoptosis and activation of caspase‐9 and ‐3. Overexpression of a constitutively active Akt mutant blocked arctigenin‐induced apoptosis. Combinational treatment with arctigenin and the PI3‐K inhibitor LY294002 significantly enhanced apoptosis. Arctigenin reduced the expression of Bcl‐xL, Mcl‐1, and survivin and the phosphorylation of mTOR and S6K, which were significantly reversed by overexpression of constitutively active Akt. This is the first report about the anticancer activity of arctigenin in HCC cells, which is mediated by inactivation of PI3‐K/Akt signaling.